2011
DOI: 10.4315/0362-028x.jfp-11-193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozone Treatment on the Safety and Quality of Malting Barley

Abstract: Molds and their mycotoxins are an expensive problem for the malting and brewing industries. Deoxynivalenol (DON) is a mycotoxin that is associated with Fusarium spp. These fungi frequently cause Fusarium head blight in wheat and barley in the midwestern region of the United States; Manitoba, Canada; Europe; and China. Barley growers and malt producers would benefit from a postharvest control method for mold growth and DON production. We evaluated the use of gaseous ozone (O(3)) for preventing Fusarium growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Foam stability and physical-chemical characteristics also do not undergo any changes [52]. Gaseous ozone can also significantly reduce Fusarium fungi when applied during steeping, without any negative consequences for malt quality [66,67].…”
Section: Chemicalsmentioning
confidence: 99%
“…Foam stability and physical-chemical characteristics also do not undergo any changes [52]. Gaseous ozone can also significantly reduce Fusarium fungi when applied during steeping, without any negative consequences for malt quality [66,67].…”
Section: Chemicalsmentioning
confidence: 99%
“…The application of gaseous O 3 was reported as more useful and most of the reviewed experiments (79%) documented the higher effectiveness and the practical advantages of a gaseous application of O 3 than aqueous solutions. This method is a more useful type of application and it has been successfully used in reducing mycotoxin accumulation in many kinds of food/feed products (e.g., cereals [ 121 , 122 , 123 ], dried fruits [ 124 ], and poultry [ 125 ]). The residual 21% were experimental studies focused on demonstrating the suitability of ozonated water for the mycotoxin inactivation in raw materials that require an aqueous disinfection step and that must be washed [ 90 , 126 , 127 , 128 , 129 , 130 ].…”
Section: Mycotoxin Detoxification In Food and Feed By Ozonementioning
confidence: 99%
“…It was also found that the treatment efficacy depends on ozone concentration, relative humidity and treatment temperature. Dodd et al (2011) investigated the effect of ozonation on malting barley-the treatment did not lead to significant reductions in aerobic plate counts, but it decreased mold and yeast counts by 1.5-log in the final malt. In the study, gaseous ozone did not negatively influence any aspect of malt quality.…”
Section: )mentioning
confidence: 99%